BUCKLING COMMUNICATION MODEL WITH CIRCULATION FORCES IN WHEEL-RAIL SYSTEMS - Victor P. Lapshin (Advanced Engineering Research, 2011)
The model that registers deformations in the friction units of the wheel-bearing type is presented. The model permits to estimate the impact of the control system dynamics on the deformation degree of the contact surfaces and conversely. The origination specification of the rail wave deformation in the railway transportation is offered.